The Simplicity of the Prophet Muhammad: A Solution to the Current Materialism Crisis - Endang Nur Fitriani; Lina Pusvisasari; Siti Mursalina; Syifa Alawiyah (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study is motivated by the phenomenon of today's consumerist lifestyle that is contrary to the simplicity of life of the Prophet Muhammad. The occurrence of consumerism is caused by technological advances and the spread of the culture of hedonism. This action proves that humans have not been able to fully realize the mandate and responsibility ordered in the Koran and Hadith. Rasulullah SAW has taught Muslims to live simply. The purpose of this paper is to compare the life of consumerism with the simplicity of life of the Prophet Muhammad. The research method used is the literature study method. In this approach, researchers collect, analyze, and discuss information from various existing sources to formulate conclusions or new views.